Pupillary response abnormalities in depressive disorders. (30th December 2016) - Laurenzo, Scott A.; Kardon, Randy; Ledolter, Johannes; Poolman, Pieter; Schumacher, Ashley M.; Potash, James B.; Full, Jan M.; Rice, Olivia; Ketcham, Anna; Starkey, Cole; Fiedorowicz, Jess G.
Abstract: Depressive disorders lack objective physiological measurements to characterize the affected population and facilitate study of relevant mechanisms. The melanopsin-mediated light signaling pathway may contribute to seasonal variation and can be measured non-invasively by pupillometry. We prospectively studied changes in melanopsin-mediated pupillary constriction in 19 participants with major depressive disorder (MDD) and 10 control across the summer and winter solstices. The melanopsin-mediated response, as measured by the pupil's sustained constriction six s after a high intensity blue light stimulus, was marginally attenuated in those with MDD relative to controls ( p =0.071). The participants with MDD unexpectedly showed a significantly reduced transient pupillary response to low intensity red ( p =0.011) and blue light ( p =0.013), but not high intensity red and blue light. Sustained pupillary constriction in response to high intensity blue light was more pronounced with increasing daylight hours ( p =0.037) and was more strongly related to objectively measured versus estimated light exposure. Melanopsin-mediated impairments in pupil response may serve as a biological marker for vulnerability to depression in low light conditions. Assessment of these and other responses to light stimuli, such as response to low intensity light, may be useful for the study of the neurobiology of MDD and related mood disorders. Highlights: Melanopsin-mediated pupillary constriction is decreased in major depression. Melanopsin-mediated pupillary constriction is more variable in major depression. Pupillary constriction is also reduced in low light rod-cone mediated pathways.